The Unexpected Ovarian Pregnancy at Laparoscopy: A Review of Management - Meher Tabassum; Kiran Atmuri (Case Reports in Obstetrics and Gynecology)
Ovarian ectopic pregnancies are a rare occurrence; however the incidence is on the rise. Preoperative diagnosis remains difficult due to nonspecific clinical symptoms and USS findings. Most patients undergo diagnostic laparoscopy with subsequent surgical management. We present the case of a 32-year-old female who presented with vaginal bleeding and an unsited pregnancy, with a BhCG of 24693. Formal USS described unruptured right tubal ectopic with ovarian pregnancy being diagnosed at laparoscopy. A wedge resection was conducted to preserve ovarian function. Postoperative recovery was uneventful and BhCG levels returned to zero (nonpregnant) in an outpatient setting. Although laparoscopy remains the gold standard of diagnosis and treatment, in this case report we discuss benefits of early diagnosis for fertility conserving management, including nonsurgical options.